2003
DOI: 10.1016/j.bbrc.2003.10.066
|View full text |Cite
|
Sign up to set email alerts
|

La, PTB, and PAB proteins bind to the 3′ untranslated region of Norwalk virus genomic RNA

Abstract: Noroviruses are human enteric caliciviruses for which no cell culture is available. Consequently, the mechanisms and factors involved in their replication have been difficult to study. In an attempt to analyze the cis- and trans-acting factors that could have a role in NV replication, the 3(')-untranslated region of the genome was studied. Use of Zuker's mfold-2 software predicted that NV 3(')UTR contains a stem-loop structure of 47 nts. Proteins from HeLa cell extracts, such as La and PTB, form stable complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
51
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 29 publications
7
51
0
Order By: Relevance
“…La interacts with the 5= and 3= ends of the Japanese encephalitis virus genome (69,70) and contributes to the translation of a subset of cellular mRNAs known as TOP mRNAs (41). We identified La protein in purifications prepared using either the 5= or 3= extremities of the MNV genomic RNA (Table 1); these proteins have also been reported for Norwalk virus (25,27), further confirming the utility of MNV as a model for studying aspects of human norovirus biology. La immunoprecipitation demonstrated an association, either direct or indirect, with the viral replication complex (Fig.…”
Section: Figsupporting
confidence: 64%
See 2 more Smart Citations
“…La interacts with the 5= and 3= ends of the Japanese encephalitis virus genome (69,70) and contributes to the translation of a subset of cellular mRNAs known as TOP mRNAs (41). We identified La protein in purifications prepared using either the 5= or 3= extremities of the MNV genomic RNA (Table 1); these proteins have also been reported for Norwalk virus (25,27), further confirming the utility of MNV as a model for studying aspects of human norovirus biology. La immunoprecipitation demonstrated an association, either direct or indirect, with the viral replication complex (Fig.…”
Section: Figsupporting
confidence: 64%
“…While to date there has been limited information regarding the role of host nucleic acid-binding proteins in the norovirus life cycle, previous studies demonstrated that a number of host factors interact with the Norwalk virus genome. Specifically, La, PTB, and PABP interact with the 3= untranslated region (UTR) of the Norwalk virus genome (27), and La, PTB, PCBP-2, and hnRNPL interact with the 5= end (25). While a functional role for these interactions is yet to be determined, due to the lack of an amenable functional assay, studies have indicated that cellular proteins may contribute to genome circularization via interactions with the 5= and 3= extremities of the viral genome (60).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Other candidates that might interact with PTB are the cold shock domain (CSD) containing protein, which was found in complex with PTB on vascular endothelial growth factor mRNA (Coles et al, 2004) and PSH, p54(nrb) and U1A, which bind together with PTB to the COX-2 3'-UTR (Hall-Pogar et al, 2007). In addition, it has been observed that PTB bind together with La to the 3'-UTR of the Norwalk virus RNA (Gutiérrez-Escolano et al, 2003). It is therefore likely that the cooperate binding of PTB and various other RNA-binding proteins results in stabilization of the mRNAs.…”
Section: Ptb Co-operativety With Other Mrna-binding Proteinsmentioning
confidence: 99%
“…The 5=-end sequence of both the genomic and subgenomic RNAs is highly conserved among several members of the family Caliciviridae (14,15). Moreover, their 5=-and 3=-end regions contain several conserved RNA secondary structures, with various sizes and positions, implicated in viral replication (16)(17)(18), as well as viral pathogenesis (14).…”
mentioning
confidence: 99%